1979
DOI: 10.1007/bf02618107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of some antibiotics on the growth of human diploid skin fibroblasts in cell culture

Abstract: During serial subcultures 50 micrograms per ml gentamicin and penicillin (100 U per ml)-streptomycin (100 micrograms per ml) depressed cell growth signficantly 2 weeks after the addition of the antibiotics; gentamicin, but not penicillin-streptomycin, stimulated cell growth before it became inhibitory. Removal of the antibiotics resulted in the cell yield returning to normal. The results show that these antibiotics can be harmful to cells even at concentrations thought to be safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…A notable bacteriostatic activity of streptomycin towards MAC inside phagocytic cells was observed Ashtekar et al 1991). We observed only a mild MAC growth inhibition with streptomycin (100 μg/ml), as reported by Goetz et al (1979). However, in agreement with Buehring et al (1995), we did not succeed in fully eradicating MAC with this antibiotic in "nonprofessional" phagocytic cells.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…A notable bacteriostatic activity of streptomycin towards MAC inside phagocytic cells was observed Ashtekar et al 1991). We observed only a mild MAC growth inhibition with streptomycin (100 μg/ml), as reported by Goetz et al (1979). However, in agreement with Buehring et al (1995), we did not succeed in fully eradicating MAC with this antibiotic in "nonprofessional" phagocytic cells.…”
Section: Resultssupporting
confidence: 88%
“…However, degeneration of the treated cells was observed after 3 d of gentamicin treatment. Higher concentrations of gentamicin were never tested, as they become rapidly toxic for cultured mammalian cells (Goetz et al 1979;Sha and Schacht 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Recently there has been a renewed debate about the etiology of this neutropenia, whether an immune mechanism is involved similar to that of penicillin-induced hemolytic anemia or whether a direct cellular effect on bone marrow precursors is responsible (Neftel et al, 1981;Murphy et al, 1983). It has been known for some time (Goetz et al, 1979;Vonen et al, 1982) that penicillin can have an antiproliferative effect in vitro without affecting cell viability. Recently Neftel et al (1985) showed that BLAs can inhibit the production of colonies in agar by human bone marrow cells, and suggested that inhibition is related to the risk of neutropenia following high-dose parenteral therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics, such as gentamicin and streptomycin, are commonly used in cell culture medium to combat bacteria found within the cells and any outside contamination. Both of these antibiotics have been linked to a depression of cell growth in mammalian cultures and to a decrease in the use of aseptic techniques and concern for increasing the likelihood of developing antibiotic resistant strains of bacteria 17,18 . Antibiotics should not be used excessively; however, their use is necessary for preventing cell culture contamination issues.…”
Section: Discussionmentioning
confidence: 99%